Identification of Institutional Role in Development Clove Agribusiness in the City of Tidore Islands - Azizah HS, Nur (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Clove agribusiness management requires institutional improvement efforts. This study aims to identify and analyze institutional roles related to the development of clove agribusiness in Tidore Kepulauan City. This research was carried out for 2 months starting from January-February 2021 in East Tidore District, Tidore City Islands. The research method used is a qualitative descriptive method. Based on the results of the research it shows that there are 8 (eight) types of institutions involved in the development of clove agribusiness including: 1). Farmers Group which acts as a forum for cooperation in clove agribusiness activities. 2). Gapoktan as a forum for mediating the extension of government programs in carrying out policies in the agricultural sector. 3). The Department of Agriculture plays a role in facilitating farmers in clove farming activities through various activities including providing assistance with ready-to-plant clove seeds and providing road infrastructure. 4). The Office of Perindagkop and UKM plays a role in monitoring the use of measuring, measuring and weighing instruments in trading activities for food needs. 5). The Agricultural Extension Center has a role as an institution that conveys government policies. 6). The Regional Public Company (Perumda) plays a role in purchasing cloves at prices prevailing in Ternate 7). Traders of Production Facilities play a role in providing production facilities such as seeds, fertilizers, medicines and agricultural tools. 8). Collector traders play a role in buying clove products from farmers.